Remote ischemic conditioning for acute ischemic stroke part 2: Study protocol for a randomized controlled trial - Ishizuka, Kentaro; Hoshino, Takao; Toi, Sono; Mizuno, Takafumi; Hosoya, Megumi; Saito, Moeko; Sato, Yasuto; Yagita, Yoshiki; Todo, Kenichi; Sakaguchi, Manabu; Ohashi, Takashi; Maruyama, Kenji; et al. (Frontiers in Neurology, 2022)
Background Remote ischemic conditioning (RIC) refers to the application of repeated short periods of ischemia intended to protect remote areas against tissue damage during and after prolonged ischemia. Aim We aim to evaluate the efficacy of RIC, determined by the modified Rankin Scale (mRS) score at 90 days after stroke onset. Design and methods This study is an investigator-initiated, multicenter, prospective, randomized, open-label, parallel-group clinical trial. The sample size is 400, comprising 200 patients who will receive RIC and 200 controls. The patients will be divided into three groups according to their National Institutes of Health Stroke Scale score at enrollment: 5–9, mild; 10–14, moderate; 15–20, severe. The RIC protocol will be comprised of four cycles, each consisting of 5 min of blood pressure cuff inflation (at 200 mmHg or 50 mmHg above the systolic blood pressure) followed by 5 min of reperfusion, with the cuff placed on the thigh on the unaffected side. The control group will only undergo blood pressure measurements before and after the intervention period. This trial is registered with the UMIN Clinical Trial Registry (https://www.umin.ac.jp/: UMIN000046225). Study outcome The primary outcome will be a good functional outcome as determined by the mRS score at 90 days after stroke onset, with a target mRS score of 0–1 in the mild group, 0–2 in the moderate group, and 0–3 in the severe group. Discussion This trial may help determine whether RIC should be recommended as a routine clinical strategy for patients with ischemic stroke.